2017
DOI: 10.1111/cas.13463
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: The translation of big genomic data to cancer precision medicine

Abstract: Cancer is a complex genetic disease that develops from the accumulation of genomic alterations in which germline variations predispose individuals to cancer and somatic alterations initiate and trigger the progression of cancer. For the past 2 decades, genomic research has advanced remarkably, evolving from single‐gene to whole‐genome screening by using genome‐wide association study and next‐generation sequencing that contributes to big genomic data. International collaborative efforts have contributed to cura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 100 publications
(176 reference statements)
0
76
0
1
Order By: Relevance
“…The identification of genetic profiles related to the susceptibility, progression and prognosis of mammary neoplasia is of paramount importance in a clinical context. Recognizing high‐risk genetic profiles could allow the establishment of preventive and surveillance protocols, as well as the implementation of individualized therapeutic measures appropriated for a specific patient at a defined time, which constitutes the basis of personalized cancer medicine …”
Section: Discussionmentioning
confidence: 99%
“…The identification of genetic profiles related to the susceptibility, progression and prognosis of mammary neoplasia is of paramount importance in a clinical context. Recognizing high‐risk genetic profiles could allow the establishment of preventive and surveillance protocols, as well as the implementation of individualized therapeutic measures appropriated for a specific patient at a defined time, which constitutes the basis of personalized cancer medicine …”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, these features make it difficult to rule out familial inheritance, but on the other hand favor our hypothesis of using holistic germline information to characterize sporadic-like TNBC. Our approach assumes that rare non-synonymous germline mutations predispose individuals in a population to cancer, whereas somatic mutations initiated and triggered the progression of the cancer (55). Furthermore, we postulated that breast cancer is a 'bubbling' and persistent pathogenic stress on the female population, and that resistance against this stress is evolutionary selected.…”
Section: Discussionmentioning
confidence: 99%
“…Their intrinsic physical properties are particularly interesting for simultaneous drug delivery, molecular imaging and applications such as localized hyperthermia (Bender et al 2018;Iv et al 2015). These technical features provide special perspectives for breast cancer treatment and diagnosis, which is especially important because of the high incidence, drug resistance and recurrence risk related to this disease (Low et al 2018;Harmon et al 2015;Karakatsanis et al 2016). Current studies with maghemite nanoparticles, an iron oxide compound, have demonstrated in vitro and in vivo specific cytotoxic action for target cells, and these results have indicated this nanoparticle as a promising option for drug delivery (Manikandan et al 2018;Chaves et al 2017;Magro et al 2018).…”
Section: Introductionmentioning
confidence: 99%